2018
DOI: 10.1111/jdv.14759
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive cutaneous and systemic features associated with specific antimyositis antibodies in adults with dermatomyositis: a prospective multicentric study of 117 patients

Abstract: Recognition of the adult DM phenotype associated with MSAs would allow more accurate appraisal of the risk of cancer, ILD and calcinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 70 publications
(235 reference statements)
7
31
0
Order By: Relevance
“…Cancer types are comparable to those in the general population stratified by age and sex, but some rare cancers, i.e., gastric or thymus cancers, may also be found (6). Clinically, anti TIF1γ-positive adult DM is associated with severe cutaneous signs, moderate muscu lar symptoms, and frequent dysphagia, while systemic features are uncommon (11,16). Other reported risk factors for cancer in adult DM, i.e., older age, male sex, and cutaneous necro sis, have also been identified in anti TIF1γ-positive adult DM (10,(16)(17)(18)(19).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Cancer types are comparable to those in the general population stratified by age and sex, but some rare cancers, i.e., gastric or thymus cancers, may also be found (6). Clinically, anti TIF1γ-positive adult DM is associated with severe cutaneous signs, moderate muscu lar symptoms, and frequent dysphagia, while systemic features are uncommon (11,16). Other reported risk factors for cancer in adult DM, i.e., older age, male sex, and cutaneous necro sis, have also been identified in anti TIF1γ-positive adult DM (10,(16)(17)(18)(19).…”
mentioning
confidence: 93%
“…Numerous autoantibodies have been identified in DM, such as anti-Mi 2, anti-melanoma differentiation-associ ated protein 5, anti-small ubiquitin like modifier activating enzyme, anti-transcription intermediary factor 1 (anti TIF1γ), and anti-nuclear matrix protein 2 (anti NXP2). Each of them defines a specific form of DM (8)(9)(10)(11)(12)(13). Anti TIF1γ autoantibodies are present in 20-30% of adult DM cases and are strongly associated with cancer, with associated cancer occurring in 18-80% of patients (6,7,14,15).…”
mentioning
confidence: 99%
“…The relationship between anti-TIF-1γ autoantibody and cancer-associated DM (CAD) was first noted in a series of 45 adult DM with an odds ratio (OR) for CAD in the presence of anti-TIF-1γ autoantibody of 48.18 (95% confidence intervals (95% CI): 2.46-943.31) (13). Multiple cohort studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) then continued to investigate the risk of CAD in the presence of anti-TIF-1γ autoantibody, but mostly in limited series. Two meta-analyses performed on 6 (312 patients) (13,(16)(17)(18)(19)(20) and 8 (408 patients) (13,(16)(17)(18)(19)(20)(21)25) cohort studies, respectively, found a pooled OR for CAD of 27.26 (95% CI 6.59-118.82) (36) and a relative risk (RR) for CAD of 5.57 (95% CI 2.91-10.65) in the presence of anti-TIF-1γ autoantibody (12).…”
mentioning
confidence: 99%
“…In an attempt to classify subgroups of dermatomyositis, a specific pattern of myositis‐specific autoantibodies (MSAs) was found in 47.1% of 117 patients. 13.7% of patients showed antimelanoma differentiation‐associated protein‐5 antibodies going along with a significantly increased appearance of violaceous macules/papules (OR 9.9) …”
Section: Autoimmune Diseasementioning
confidence: 99%
“…13.7% of patients showed antimelanoma differentiation-associated protein-5 antibodies going along with a significantly increased appearance of violaceous macules/papules (OR 9.9). 7 There is a common consensus that smoking is bad for your health; however, there are several conditions where smoking may have positive effects, for instance farmer's lung or certain diseases of the oral mucosa. In a systematic literature review, the effect of cigarette smoking was studied in a pooled data analysis in patients with pemphigus vulgaris.…”
Section: Autoimmune Diseasementioning
confidence: 99%